Highly Thermally Conductive Polymer/Graphene Composites with Rapid Room-Temperature Self-Healing Capacity - Yu, Huitao; Chen, Can; Sun, Jinxu; Zhang, Heng; Feng, Yiyu; Qin, Mengmeng; Feng, Wei (Nano-Micro Letters, 2022)
Composites that can rapidly self-healing their structure and function at room temperature have broad application prospects. However, in view of the complexity of composite structure and composition, its self-heal is facing challenges. In this article, supramolecular effect is proposed to repair the multistage structure, mechanical and thermal properties of composite materials. A stiff and tough supramolecular frameworks of 2-[[(butylamino)carbonyl]oxy]ethyl ester (PBA)–polydimethylsiloxane (PDMS) were established using a chain extender with double amide bonds in a side chain to extend prepolymers through copolymerization. Then, by introducing the copolymer into a folded graphene film (FGf), a highly thermally conductive composite of PBA–PDMS/FGf with self-healing capacity was fabricated. The ratio of crosslinking and hydrogen bonding was optimized to ensure that PBA–PDMS could completely self-heal at room temperature in 10 min. Additionally, PBA–PDMS/FGf exhibits a high tensile strength of 2.23 ± 0.15 MPa at break and high thermal conductivity of 13 ± 0.2 W m−1 K−1; of which the self-healing efficiencies were 100% and 98.65% at room temperature for tensile strength and thermal conductivity, respectively. The excellent self-healing performance comes from the efficient supramolecular interaction between polymer molecules, as well as polymer molecule and graphene. This kind of thermal conductive self-healing composite has important application prospects in the heat dissipation field of next generation electronic devices in the future. Highlights: 1 PBA–PDMS/folded graphene film (FGf) composite with high strength and thermal conductivity and rapid self-healing capacity at room temperature is prepared. 2 PBAx–PDMS/FGf self-healed its strength, thermal conductivity, and conductivity and the self-healing mechanism of thermal conductivity is also proposed. 3 PBA–PDMS/FGf has significant application potential in interface thermal conductivity and robot skins.